2023
DOI: 10.3390/ijms24043900
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila as a Next-Generation Probiotic in Modulating Human Metabolic Homeostasis and Disease Progression: A Role Mediated by Gut–Liver–Brain Axes?

Abstract: Appreciation of the importance of Akkermansia muciniphila is growing, and it is becoming increasingly relevant to identify preventive and/or therapeutic solutions targeting gut–liver–brain axes for multiple diseases via Akkermansia muciniphila. In recent years, Akkermansia muciniphila and its components such as outer membrane proteins and extracellular vesicles have been known to ameliorate host metabolic health and intestinal homeostasis. However, the impacts of Akkermansia muciniphila on host health and dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 190 publications
0
23
0
Order By: Relevance
“…63 Therefore, future studies should consider the differences in strain, specific host conditions, and mouse strain when evaluating the therapeutic effects of Akk in the treatment of human inflammation including IBD and colitis. 63…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…63 Therefore, future studies should consider the differences in strain, specific host conditions, and mouse strain when evaluating the therapeutic effects of Akk in the treatment of human inflammation including IBD and colitis. 63…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that elevated Akk abundance is positively correlated with worsening of host disease progression. 63 For some specific conditions, Akk promotes colitis and exacerbates the progression of inflammation. For example, Akk exacerbates the inflammatory response caused by murine Salmonella enterica Typhimurium and DSS.…”
Section: Food and Function Papermentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Graner and colleagues found that when compared to those without alcohol-related liver disease (ALD) those with ALD exhibited decreased relative abundance of Akkermansia muciniphila , an intestinal commensal that promotes barrier function in part by enhancing mucus production (54). Recent interventions have used probiotic supplementation of Akkermansia for several health outcomes (55, 56), and it might have potential for those with a history of homelessness; however further research is required. While the observed Akkermansia trend was as expected, finding lower Prevotella 9 in Veterans with no history of homelessness was unexpected.…”
Section: Discussionmentioning
confidence: 99%